Seed treatment formulation of Trichoderma and Gliocladium for biological control of Macrophomina phaseolina in sesamum - R. JEYARAJAN, P. SANKAR and (Indian Phytopathology, 2002)
The viability of Trichoderma and Gliocladium in talc based powder formulation and treated sesame seeds was estimated. The number of c.f.u. of Trichoderma spp. and G. virens in fresh product ranged from 224-297X106/g in different species. The population of antagonists was reduced by 19, 21, 21 and 29.9% in T. viride, T. harzianum, T. longibrachiatum and G. virens, respectively, after 75 d of storage. After 120 d c. 50% of the population was retained. In treated seeds there was a negligible reduction in the population of antagonists after 45 d and then a slight decrease. After 120 d 55-68% of the initial population was maintained.